A Framework for Measuring Knowledge Transfer Process in E-Learning Environment - Abdullah, Salfarina (2006)
Efficiently transferring knowledge has proven to be a difficult challenge as well as to get people to use the knowledge (Seidman and McCauley, 2005). And as a part of ensuring that the knowledge transfer process is effectively conducted, there is a strong needs to measure its effectiveness. Although research in this area has been conducted in many settings, unfortunately less attention has been paid to examine the process in the virtual environment (Sarker, 2003), including the E-Learning. This may be due to the fact that lack of research has been found so far, which addressed a formal or specific guideline (or framework) for measuring the effectiveness of knowledge transfer process in E-Learning. As stated by Tillquist and Rodgers (2002), the existing measures often appear confusing and may not provide a satisfactory description of the process’s effectiveness. Looking at the huge influence that E-Learning brought to Knowledge Transfer Process has motivates the attempt for developing the effectiveness measurement framework for knowledge transfer process in E-Learning environment. This framework is inspired from the E-Faculty, chosen as the case of this research. It is an E-Learning system developed by FSKTM, UPM as complement to the traditional classroom.